Pemanfaatan Perpustakaan Sekolah Sebagai Sumber Belajar Di Sekolah Menegah Atas - Togarman Damanik; Ulung Napitu; Hisarma Saragih (Journal on Education, 2023)
This study aims to examine the benefits of the school library as a learning resource for high school students. In achieving this goal, it is necessary to have facilities and infrastructure that can support the availability of learning resources and one of these learning resources is the library. The research method used is research. Literature (Library Research) is a type of Qualitative Research, Research whose object of study uses library data in the form of books as a data source. Reading, analyzing and analyzing various literatures. teaching and learning in realizing educational goals. in Law no. 2 of 2003 concerning the National Education System in Article 3 states that the purpose of education is to develop the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, have faith, are capable, creative, independent and become citizens of a democratic and responsible. In achieving these goals, facilities and infrastructure are needed that can support these goals through the availability of learning resources and one of these learning resources is the library. Formal or schools run by the government or the community or informally must provide learning resources. One of the most important learning resources in schools is the school library. The school library not only provides reading material to increase knowledge and insight for students, but is also an integral part of learning. The use of school libraries in the world of education is very important, namely to assist the implementation of quality education. Because the school library is one of the learning resources in schools, therefore, the library must carry out its function properly to provide information needed by students and teachers.